Performing the unnameable : an anthology of Australian performance texts - Allen, Richard James, 1960-; Pearlman, Karen, 1960-; RealTime (Sydney : Currency Press in association with RealTime, 1999)
This is the first collection of performance texts created by Australian performers, performance companies and writers. It pays tribute to the largely undocumented work of a generation of artists working across the boundaries of theatre, performance, performance art and new media.
Keywords: Performance art -- Australia; Theater -- Australia